On generalized vector quasi-equilibrium problems - Li, S.; Teo, Kok; Yang, X. (Yokohama Publishers, 2007)
This paper deals with generalized vector quasi-equilibrium problems. Using a nonlinear scalarization function and Ky Fan minimax inequality, existence theorems for two classes of generalized vector quasi-equilibrium problems are established.